2002
DOI: 10.1136/gut.51.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Related IgA1 and IgG producing cells in blood and diseased mucosa in ulcerative colitis

Abstract: Background: Ulcerative colitis (UC) is a chronic inflammatory bowel disease in which the colonic mucosa is infiltrated with plasma cells producing IgG autoantibodies. It is not known whether this represents a local mucosal response which has switched to IgG or a peripheral response which may have been initiated by peripheral antigen which homed to the colonic mucosa. The clonal distribution of IgG secreting cells and isotype switched variants in UC is not known. Aims: To investigate the clonal distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
2
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 26 publications
1
28
2
1
Order By: Relevance
“…Lineage tree characteristics (described below) were analyzed using our MTree r program [60,61], and compared with samples taken from healthy intestinal tissue of intestinal carcinoma cases. The results of our analysis confirm that diversification processes do occur in B-cell clones found in the inflamed and healthy intestinal tissues [59]. Most importantly, our finding of clonal relationships between …”
supporting
confidence: 78%
“…Lineage tree characteristics (described below) were analyzed using our MTree r program [60,61], and compared with samples taken from healthy intestinal tissue of intestinal carcinoma cases. The results of our analysis confirm that diversification processes do occur in B-cell clones found in the inflamed and healthy intestinal tissues [59]. Most importantly, our finding of clonal relationships between …”
supporting
confidence: 78%
“…3 In UC, the inflammatory cell infiltrate is characterized by a large number of plasma cells secreting IgG, which by binding complement contributes to tissue damage and ongoing disease. 4 Within IBD, there is a subgroup of patients who develop primary sclerosing cholangitis (PSC), a chronic fibrosing liver disease characterized by progressive destruction of both intrahepatic and extrahepatic bile ducts by a combination of inflammation and fibrosis. 5 A majority of PSC patients have UC (60-100%), whereas a much smaller number of UC patients develop the liver disease (2.4-7.5%) in Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of highly related and even identical V H sequences between the cervical mucosa and the peripheral blood compartments is of particular interest because, to the authors' knowledge, this is the first time this has been seen. While highly specific CDR3 clone specific primers have been used to identify related IgG clones in different compartments, 60 they do not permit an evaluation of the frequency of the observed clones. Our use of V H family specific primers in the present study, while biased to germline encoded V gene families, is relatively non-biased to combinatorial assemblages; indeed, it is of much lower bias than targeting a somatically combined CDR region as in Thoree et al 60 and this allows us to make conclusions about the regularity of observed clones.…”
Section: Discussionmentioning
confidence: 99%
“…While highly specific CDR3 clone specific primers have been used to identify related IgG clones in different compartments, 60 they do not permit an evaluation of the frequency of the observed clones. Our use of V H family specific primers in the present study, while biased to germline encoded V gene families, is relatively non-biased to combinatorial assemblages; indeed, it is of much lower bias than targeting a somatically combined CDR region as in Thoree et al 60 and this allows us to make conclusions about the regularity of observed clones. The identification of related CMC and PBMC clones does not necessarily imply that the observed mucosal response is of peripheral origin, as B cells migrate to other mucosal tissues via the blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation